Performance of marrow stromal cell-seeded small-caliber multilayered vascular graft in a senescent sheep model. (14th June 2018) - Madhavan, Krishna; Elliot, Winston; Tan, Yan; Monnet, Eric; Tan, Wei
Abstract: Failure of small-caliber grafts, used as bypass or reconstructive grafts in cardiovascular treatments, is often caused by thrombosis and stenosis. We have developed a multilayered, compliant graft with an electrospun heparin-encapsulated core and collagen-chitosan shell. Herein, the performances of acellular and cell-seeded grafts were evaluated in adult sheep for preclinical assessment. Allogeneic ovine marrow stroma cells (MSCs) were uniformly attached to the lumen of cell-seeded grafts. Interposition grafts were used for carotid arteries. Four grafts were tested for each type. Upon implantation, all grafts successfully restored perfusion and rhythmically deformed under pulsatile arterial flow. Weekly ultrasonography and Doppler revealed that all grafts remained patent for perfusion during the course of one-month study. No formation of blood clots or other complications were found. The diameter of graft lumen did not vary significantly over the time or with the graft type, while narrowing at anastomosis and significant thickening of graft wall were found in both types of grafts. More significant neotissue formation was found at anastomotic sections of acellular controls compared to cell-seeded grafts. Results from histological and immunofluorescent analyses revealed moderate intimal hyperplasia (IH) at anastomosis. When compared to cell-seeded grafts, acellular controls presented thicker IH composed of α-smooth muscle actin positive cells and ground substances, which correlated with reduced and more disturbing flow. IH was thickest at anastomosis and tapered off to a minimum in the mid-section. Few PECAM-positive cells appeared on cell-seeded grafts but not acellular controls. Additionally, lesser graft thickening was found in cell-seed grafts, which might be associated with the function of stromal cells in altering the fibrotic process during tissue repair. Results suggest that MSCs held the potential to reduce hyperplasia and improve healing in an aged, large animal model for vascular grafting.